Modality preference and learning style theories: rethinking the role of sensory modality in learning. Issue 1 (2nd January 2016) - Lodge, Jason M.; Hansen, Louise; Cottrell, David
Abstract : Learning styles have been widely accepted in pedagogical practice but suffer from a distinct lack of empirical support. While a diverse range of learning styles have been proposed, modality preference has received the most attention within educational research and practice. Supporters of this theory posit that each individual has a dominant sense and that when new material is presented in this preferred modality, learning is improved. For the most part this theory has been debunked, however, it leaves open the question of exactly how sensory modality influences learning. This critical review identifies methodological limitations in previous research and provides a perspective from psychological science, which supports the implausibility of modality preference as a basis for instructional design. To extend on the existing literature, an alternative position is presented suggesting that modality effects are task dependent, hence modality matters, but it matters for everyone in the same way depending on the nature of the learning activity.